PERAN DPRD DALAM PENJARINGAN ASPIRASI MELALUI MUSRENBANG KOTA DENPASAR PERIODE 2012-2013 - Krisna Dewi, Eka Wahyu; Erviantono, S.IP, M.Si, Tedi; S.Fil, M.A, Bandiyah (CITIZEN CHARTER, 2015)
ABSTRACT The aim of this study is to know the role of DPRD in Musrenbang mentoring and involvement process between executive and legislative in order to accommodate the result of musrenbang in subtlety of the development of Denpasar City.The method of this study is descriptive qualitative. To gain the data, the researcher did the field observation and deep interview with the resource who related with the senator in taking aspiration by musrenbang Denpasar City in the 2012-2013. The results of this study are, the role of DPRD in monitoring the musrenbang was started on January in village level. On February was held in sub-district level. On March was held in regency level. The presences of the senator were four times in musrenbang meeting, those are in musrenbang RPJPD, musrenbang RPJMD, musrenbang RKPD, and musrenbang village level. The involvement process of executive and legislative in accommodate the result of musrenbang assessed not accurate. Oftentimes the DPRD was hard to find the data from SKPD. It caused by the supervision in the planning of the achievement target as the reference of the next planning was not applied yet. From the result of some documents and interview the role of DPRD is as the facilitator between one SKPD to the other SKPD. The functions taken by the DPRD are legislation function and budgeting. The other involvement between executive and legislative in designing programs and activities was overlapping between one SKPD to the other. It was marked by the same program of Disnakertan and SATPOL PP in destruction of vagrant and beggars. That overlapping cause the achievement was not optimal. Keyword: musrenbang, aspiration networking, DPRD’s role